The duration of the productive use and lifetime productivity of holsteinized black-motley cattle - S. V. Titova (Аграрная наука Евро-Северо-Востока, 2016)
In connection with the intensification of dairy farming, increasing the productivity of livestock, construction of industrial complexes productive longevity of cows has been reduced. According to research data, sires have highest influence on productive longevity of cows. The purposes of research - to study the longevity and lifetime productivity performance of cows of black-motley breed depending on the linear supplies and breediness of Holstein bulls and productive longevity of their female ancestors. Research are conducted by analyzing of data of retired breeding cows of black-motley breed and crossbred cows, obtained by crossing black-and-white Holstein breed in a "Semenov" breeding farm, Republic of Mari El. The data indicate significant influence of genotype and line affiliation of father's bull on productive longevity and lifetime yield of daughters. The descendants of black-motley breed bulls lactate 6.09 lactations and its yield was 33 437 kg of milk which is 2.56 lactations and 11510 kg of milk more than their peers. The best results on longevity and life milking were in daughters of bulls of line A. Adem (6.83 lactations and 43037 kg of milk). High levels of productive longevity (5.95 lactation) and lifetime productivity (36 075 kg of milk) had daughters of bulls, whose mothers are low life milk yield - up to 15000 kg of milk. In this group of animals, it is revealed the presence of a positive correlation between lifelong milk yield in bull mothers and productive longevity (0.66); and a lifetime milk yield in daughters (0.54). At the increase of productive longevity in bull's mothers, an increase of productive longevity and lifetime milk yield and daughters of these bulls was obtained.